Substituted N-(Biphenyl-4 '-yl)methyl (R)-2-Acetamido-3-methoxypropionamides: Potent Anticonvulsants That Affect Frequency (Use) Dependence and Slow Inactivation of Sodium Channels - Lee, Hyosung; Park, Ki Duk; Torregrosa, Robert; Yang, Xiao-Fang; Dustrude, Erik T.; Wang, Yuying; Wilson, Sarah M.; Barbosa, Cindy; Xiao, Yucheng; Cummins, Theodore R.; Khanna, Rajesh; Kohn, Harold (AMER CHEMICAL SOC, 2014)
We prepared 13 derivatives of N-(biphenyl-4'-yl)methyl (R)-2-acetamido-3-methoxypropionamide that differed in type and placement of a R-substituent in the terminal aryl unit. We demonstrated that the R-substituent impacted the compound's whole animal and cellular pharmacological activities. In rodents, select compounds exhibited excellent anticonvulsant activities and protective indices (PI = TD50/ED50) that compared favorably with clinical antiseizure drugs. Compounds with a polar, aprotic R-substituent potently promoted Na+ channel slow inactivation and displayed frequency (use) inhibition of Na+ currents at low micromolar concentrations. The possible advantage of affecting these two pathways to decrease neurological hyperexcitability is discussed.
Keywords: ION CHANNELS; ANTIEPILEPTIC DRUGS; LACOSAMIDE; EXPRESSION; LIDOCAINE; DISCOVERY; EPILEPSY; CURRENTS; TARGETS; MODELS